Technological limitations in obtaining and using cellulose biocomposites - Masek, Anna; Kosmalska, Anna (Frontiers in Bioengineering and Biotechnology, 2022)
Among the many possible types of polymer composite materials, the most important are nanocomposites and biocomposites, which have received tremendous attention in recent years. The fundamental benefits of using biocomposites as alternative materials to "petroleum-based" products are shaping current development trends and setting directions for future research and applications. A dynamic growth of the production and sale of biocomposites is observed in the global market, which results not only from the growing interest and demand for this type of materials, but also due to the fact that for the developed and modified, thus improved, materials the area of their application is constantly expanding. Already today, polymer composites with plant raw materials are used in various sectors of the economy. In particular, this concerns the automotive and construction industries, as well as widely understood packaging. Bacterial cellulose, for example, also known as bionanocellulose, as a natural polymer with specific and unique properties, has been used extensively, primarily in numerous medical applications. Intensive research is also being carried out into composites with natural fibres composed mainly of organic compounds such as cellulose, hemicellulose and lignin. However, three aspects seem to be associated with the popularisation of biopolymers: performance, processing and cost. This article provides a brief overview of the topic under discussion. What can be the technological limitations considering the methods of obtaining polymer composites with cellulose filler? What properties of cellulose constitute an important issue from the point of view of its applicability in polymers, in the context of compatibility with the polymer matrix and processability? Various studies discuss the comparison in terms of production, properties and highly demanding applications of plant or bacterial cellulose. Usually, aspects of each are described separately in the literature. In the present review, several important data are gathered in one place, providing a basis for comparing the types of cellulose described. There still seems to be considerable potential to improve the cellulosic material composites being produced and the efficiency of their manufacturing. Thus, the material still needs to be well optimized before it can replace conventional materials at the industrial level in the near future.